(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Three lichen taxa viz. Aspicilia asiatica (H. Magn.) Yoshim., Lecanora subcarnea (Sw.) Ach. var. soralifera H. Magn., and Thelidium minutulum Körb. were identified as new to Turkey as a result of a lichenological survey in the Bitlis and Mu? regions Turkey. In addition, Lecanora subcarnea var. soralifera is also new to Asia. A detail taxonomic account, notes on known distribution, substrates, and chemistry under each taxon and comparisons with morphologically similar taxa are furnished under each taxon. Keywords: Ascolichen; Lecanoraceae; Hymenchiaaceae; Verrucariaceae. Bangladesh J. Plant Taxon. 24(1): 8389, 2017 (June)